Using the conceptual map as a teaching strategy to improve reading comprehension (2019)
This article aims to describe the educational context of reading comprehension of students in 3rd and 4th grade of the educational institution “Sergio Camargo” (Miraflores, Colombia). t is intended to demonstrate the effect between the use of conceptual maps and the improvement in the reading comprehension by means of the qualitative methodology, with a critical social approach and a design based on the research-action, it can be found that the first pedagogical character that stimulates students to emulate ideas and forms of reading comprehension, is the teacher, giving examples and organizing the exercises, in such a way that if this principal agent does not find adequate strategies to improve the process of reading comprehension and he does it in a monotonous way, implicitly makes reading and reading comprehension a duty and an obligation for children. Reading in this way generates a decrease in self-interest on the students, also making it difficult for learners the chance for them to capture their own ideas. In this sense, the use of concept maps as a strategy influences reading comprehension and helps improve academic performance in a positive way, predicting the success of students.